Meat Physical Quality of Red Brahman Crossbred and Droughtmaster Cattle at Different Genders and Ages - Maulid, Shintia Sukmawati Cahya; Kuswati, Kuswati; Purwanto, Didiek; Susilo, Agus (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The meats physical quality is reflected by meat characteristics and reference for consumers to choose good quality of beef. Several factors that affect the meat quality are interaction genetic and environmental factors during maintenance until post slaughter. The research was conducted to evaluate the meat physical quality with the breeds factor (Red Brahman Crossbred and Droughtmaster), genders (steer and heifer), and ages (PI0, PI2, and PI4). The research materials were 120 samples of Longissimus dorsi ribs 12th from AM FARM abattoir and tested physical quality meat on QC Laboratory of KASA Company. The data were analyzed by ANOVA and Least Significant Difference if there were any significant. The variables observed were pH, meat color, WHC, cooking loss, and tenderness. The results showed that breeds factors have no significant difference on meat physical quality. The factor of genders nested to breeds has very significance (P<0,01) on meat physical quality except for pH and tenderness there wasn’t significant differences. The factor of ages nested to genders nested to breeds has very significant (P<0,01) on meat physical quality except that pH. The conclusion that the evaluation of meat physical quality can be predicted by the relationships of breed, genders, and age factors. Keywords: Meat physical quality, breeds, genders, ages